Peran Aqidah Dalam Membentuk Karakter Profesional yang Berintegritas - N, Nursahilin; J, Jamilatussoleha; Hidayatullah, Adelya; D, Derlina; R, Regina; Sabila, Salsa; M, Marsalina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The ethos of work in Islam does not just mean productivity, but the values, morals, and purpose of a Muslim’s life. In Islam, work is defined not only as a worldly activity, but also as an act of worship. Therefore, faith, as the foundation of faith, has a significant influence in shaping one’s work style. The results of this discussion show that a strong faith makes one honest, disciplined, responsible, and works with the intention of worship. Thus, the Islamic work ethos constitutes an important solution to answer the moral challenges of the modern era. Islamic Work Ethos through the Application of Islamic Akhlaq and Law constitutes an important effort in shaping a working environment that is ethical and grounded in Islamic principles. This study explores the role of ethics and Islamic law in shaping an Islamic work ethos. Using a qualitative approach, data were collected through interviews and document analysis. The results show that a good understanding and application of morality can improve employees’ productivity, quality of work, and job satisfaction. On the other hand, a deep understanding of Islamic law provides a solid foundation for fair and responsible business practices.Al-Ghazali. (2017).